Collaborative Annotation Redefines Gene Sets for Crucial Phytopathogens - Pedro, Helder; Yates, Andrew D.; Kersey, Paul J.; De Silva, Nishadi H. (Frontiers in Microbiology, 2019)
Accurate and comprehensive annotation of genomic sequences underpins advances in managing plant disease. However, important plant pathogens still have incomplete and inconsistent gene sets; and lack dedicated funding or teams to improve this annotation. This paper describes a collaborative approach to gene curation to address this shortcoming. In the first instance, over forty members of the Botrytis cinerea community from eight countries, with training and infrastructural support from Ensembl Fungi, used the gene editing tool Apollo to systematically review the entire gene set (11,707 protein coding genes) in 6-7 months. This has subsequently been checked and disseminated. Following this, a similar project for another pathogen, Blumeria graminis f. sp. hordei, also led to a completely redefined gene set. Currently, we are working with the Zymoseptoria tritici community to enable them to achieve the same. While the tangible outcome of these projects is improved gene sets, it is apparent that the inherent agreement and ownership of a single gene set by research teams as they undergo this curation process is consequential to the acceleration of research in the field. With the generation of large data sets increasingly affordable, there is value in unifying both the divergent data sets and their associated research teams; pooling time, expertise and resources. Community-driven annotation efforts can pave the way for a new kind of collaboration among pathogen research communities to generate well-annotated reference data sets; beneficial not just for the genome being examined but for related species and the refinement of automatic gene prediction tools.